2022
DOI: 10.3171/2021.10.jns211064
|View full text |Cite
|
Sign up to set email alerts
|

Use of surgical video–based automated performance metrics to predict blood loss and success of simulated vascular injury control in neurosurgery: a pilot study

Abstract: OBJECTIVE Experts can assess surgeon skill using surgical video, but a limited number of expert surgeons are available. Automated performance metrics (APMs) are a promising alternative but have not been created from operative videos in neurosurgery to date. The authors aimed to evaluate whether video-based APMs can predict task success and blood loss during endonasal endoscopic surgery in a validated cadaveric simulator of vascular injury of the internal carotid artery. METHODS Videos of cadaveric simulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…[1][2][3][4][5] Applying these methods to analyze surgical video from the operating room may improve patient care by detecting complications, assisting trainee development, and assessing performance. [6][7][8][9][10] Algorithmic methods thrive when presented with comprehensive data sets. Surgical video data sets, however, are traditionally collected to answer a single question by a single group of investigators, depicting a particular surgical scenario (eg, one data set for object detection in neurosurgery and a different data set for phase detection in general surgery).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] Applying these methods to analyze surgical video from the operating room may improve patient care by detecting complications, assisting trainee development, and assessing performance. [6][7][8][9][10] Algorithmic methods thrive when presented with comprehensive data sets. Surgical video data sets, however, are traditionally collected to answer a single question by a single group of investigators, depicting a particular surgical scenario (eg, one data set for object detection in neurosurgery and a different data set for phase detection in general surgery).…”
Section: Introductionmentioning
confidence: 99%
“…Advances in machine learning and computer vision (CV) facilitate the discovery of unknown patterns in large bodies of visual data . Applying these methods to analyze surgical video from the operating room may improve patient care by detecting complications, assisting trainee development, and assessing performance . Algorithmic methods thrive when presented with comprehensive data sets.…”
Section: Introductionmentioning
confidence: 99%
“…The lowest average score among the ten items was for catheter operation, which is a unique technique that cannot be obtained through the performance of open surgery. It has already been reported that physicians perform better surgery when there is smaller blood loss, and it is considered that the same applies to angiography and endovascular treatment [ 10 ]. The item procedural completion assesses whether the physician needed to be replaced by a senior physician because of dangerous or unsuccessful repeated procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The APMs were found to be more accurate predictors of surgeons’ performance than their training status or prior experience. [ 33 ] With the rapidly advancing AI technologies, robots requiring minimal human supervision have led to reduced surgical site infections, precise tumor segmentation, reduced incision, and scar size and shorter recovery spans. [ 32 ] Although these ML powered devices can have unprecedented potential of pairing with human teammates, they do not necessarily possess human teamwork competencies such as communication, coordination, and adaptation.…”
Section: Discussionmentioning
confidence: 99%